Sadomasochism in everyday life : the dynamics of power and powerlessness - Chancer, Lynn S. (Rutgers University Press, 1992)
Lynn Chancer advances the provocative thesis that sadomasochism is far more prevalent in contemporary societies like the United States than we realize. According to Chancer, sexual sadomasochism is only the best-known manifestation of what is actually a much more broadly based social phenomenon. Moving from personal relationships to school, the workplace, and other interactions, Chancer uses a variety of examples that are linked by a recurrent pattern of behavior. She goes beyond the predominantly individualistic and psychological explanations generally associated with sadomasochism (including those popularized in the "how to" literature of the recent Women Who Love Too Much genre) toward a more sociological interpretation. Chancer suggests that the structure of societies organized along male-dominated and capitalistic lines reflects and perpetuates a sadomasochistic social psychology, creating a culture steeped in everyday experiences of dominance and subordination.